Aid and forgetting the enemy: A systematic review of the unintended consequences of international development in fragile and conflict-affected situations. (June 2022) - Davidson, Angus Alexander; Young, Michael Denis; Leake, John Espie; O'Connor, Patrick
Abstract: Fragile and conflict-affected situations (FCAS) are a significant focus area of international development efforts, with corresponding sizable investments by global donors. When implementing development assistance programmes in this context, the risk of unintended consequences tends to be higher as the conflict tends to increase complexity, and typically, FCAS development programmes are designed to deliver benefits only to parties on one side of the conflict. Searching for new insights, a systematic review of 121 documents was used to identify specific types of unintended consequences, their frequency and the nature of management strategies used to address them. Examination of these documents identified aggravation of the conflict and unintended support either for the opposing side's military regime or a non-state actor was the most common unintended consequence. As nearly all assessments only considered the nature of consequences from the donor's viewpoint, we conclude that there may be a case for assessing impacts from the alternative viewpoint – that is, of unsupported parties to the conflict. More generally, we conclude that FCAS programme guidelines would benefit from the development and deployment of more rigorous evaluation methods and the codifying of unintended consequences terminology. Highlights: In FCAS development projects where or whenever one unintended consequence is identified, there will likely be more. As many as one-quarter of all FCAS development projects may have negative unintended consequences. Unintended consequences often arise from failure to account for the role that actors who have power and control can play. Evaluators are rarely asked to assess impacts from the otherviewpoint, that is, of unsupported parties to the conflict. Given the complexity in FCAS, it may be possible to reduce unintended consequences through the implementation of guidelines.